CO2 emissions for concrete bore piling construction - Nik Yahya, Nik Nurul Hidayah; Mohd. Din, Shamzani Affendy; Abdullah, Alias; T., Sugiyama; Hadi, Purwanto (Universiti Teknologi Malaysia, 2015)
Japan and Malaysia are among the sustainable countries in the world ranking 26 and 51 in the Environmental Performance Index (EPI), accordingly. Recent data obtained from the statistical department shows that both countries GDP contributed by the construction industries amounting 18.6% in Malaysia while Japan at 10% contribution in 2012. Malaysia and Japan are the countries that depend on the concrete infrastructure construction. As the development demand of the countries increase rapidly, it is a huge challenge to the construction industry player to sustain the environment from degradation. Hence, this paper offer strategic plans mitigation measures in resolving those issues. CO2 is the environmental performance indicator to be evaluated in this paper, specifically on bore piling concrete structure construction. Construction site from Malaysia had been investigated. These data are then being analysed by using the 2014 Malaysia inventory data that was developed through this study. The key finding of this research is the 2014 Malaysian energy CO2 emission inventory data, the concrete bore pile life cycle analysis for the scope of construction and transportation of materials of CO2 emissions found at 20,910.54 kg-CO2/m3. In comparison with Japanese concrete infrastructure, this amount is the highest thus proven that volume of concrete did not affect the amount of disseminated CO2 to the environment but the amount of combustion from machineries from and transportation affect the CO2 emissions. Another significant finding of this paper is the strategic mitigation measure that was done in the planning stage and imposed on site. Hence, CO2 emissions ground from the concrete construction activities are turning back its cycle by affecting construction industry itself but can be